2006
DOI: 10.1080/10473289.2006.10464430
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Banning of Two-Stroke Engines on Airborne Particulate Matter Concentrations in Dhaka, Bangladesh

Abstract: Vehicular air pollution is common in growing metropolitan areas throughout the world. Vehicular emissions of fine particles are particularly harmful because they occur near ground level, close to where people live and work. Two-stroke engines represented an important contribution to the motor vehicle emissions where they constitute approximately half of the total vehicle fleet in Dhaka city. Two-stroke engines have lower fuel efficiency than fourstroke engines, and they emit as much of an order of magnitude an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Similar scenario is also present for the second largest city of Bangladesh. Impact of banning of two-stroke engine of airborne particulate matter concentrations in Dhaka has been studied (Begum et al, 2006). Atmospheric pollution in urban areas is a major issue in many developing countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Similar scenario is also present for the second largest city of Bangladesh. Impact of banning of two-stroke engine of airborne particulate matter concentrations in Dhaka has been studied (Begum et al, 2006). Atmospheric pollution in urban areas is a major issue in many developing countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…This factor would include both cars and motorbikes. The three-wheel taxis in Dhaka all are fueled by CNG (Begum et al, 2006b).…”
Section: Results Using Total Oc and Ecmentioning
confidence: 99%
“…BC concentrations were observed to vary from month to month depending on the meteorological conditions. It has been found that the concentration has decreased relative to previous years as a result of policies adopted by the government (Begum, 2006a). PM and BC concentrations in the AirMetrics and MOUDI samples were compared.…”
Section: Pm Bc and Ec Concentrations Frommentioning
confidence: 99%
“…The HS site is a heavily traffic-impacted site while the SR site is in a residential area. The sources of the observed PM for these sites have been extensively discussed in prior source apportionment studies (Begum et al, 2010(Begum et al, , 2008(Begum et al, , 2006a(Begum et al, , b, 2004.…”
Section: Trends In Particulate Matter and Blackmentioning
confidence: 99%
See 1 more Smart Citation